Students’ self-regulated learning in open and distance learning for Mathematics course - Yahya, Nur Azila; Md Said, Junaida; Mohd Yusof, Aufzalina (EDUCATUM Journal of Science, Mathematics and Technology, 2021)
The paper presents the study on self-regulated learning (SRL) using open and distance learning (ODL) for Mathematics course in Universiti Teknologi MARA (UiTM), Perak Branch, Tapah Campus. Some concerns with ODL mode are students’ academic performance, mathematical knowledge acquired, self-regulated learning when applying ODL alone throughout the entire semester. A sample of 347 among undergraduate students were collected at the end of March – July 2020 academic semester to measure level of self-regulated learning. Descriptive analysis was used to analyze the data. The findings indicated that the level of agreement for ODL has positive contributions to the students’ SRL.